Comparative Study of Hyperbaric Bupivacaine Plus Ketamine Vs Bupivacaine Plus Fentanyl for Spinal Anaesthesia during Caeserean Section - Shrestha, SK; Bhattarai, B; Shah, R (Kathmandu University Medical Journal, 2015)
Background Spinal anesthesia is widely used for caesarean section due to its rapid onset, low failure rate, complete analgesia. Addition of intrathecal ketamine and opioids to local anaesthetics seems to improve the quality of block and prolong the duration of analgesia. Objectives The purpose of this study was to compare the effect of intrathecal ketamine mixed with hyperbaric bupivacaine to intrathecal fentanyl mixed with hyperbaric bupivacaine. Methods One hundred parturients ASA Grade I scheduled for elective or semiurgent caesarean section under spinal anaesthesia were randomly divided into two groups. Group A received 2ml (10 mg) hyperbaric bupivacaine 0.5% plus 25 mg preservative free ketamine. Group B received 2ml (10mg) hyperbaric bupivacaine 0.5% plus 25?g fentanyl. The patients were observed intraoperatively for the onset of sensory block, degree of motor block and total duration of analgesia. Results The time to achieve Bromage scale 3 motor blockade was shorter in Group A than in Group B.(p= 0.445) whereas time to achieve highest dermatomal level of sensory block was shorter in Group A than in Group B (p= 0.143). The duration of spinal analgesia was longer in Group B than in Group A (p= 0.730). The frequency of side effect such as sedation score was higher in Group A compared to Group B (p= 0.048). The incidence of pruritus was significantly higher in Group B compared to Group A (p = 0.000). Conclusion Addition of preservative free ketamine lead to faster onset of sensory and motor blockade, although it did not prolong the duration of spinal analgesia compared to addition of fentanyl in parturients undergoing caesarean section with spinal anaesthesia. Kathmandu Univ Med J 2013; 11(4): 287-291